Pengaruh Motivasi Ekonomi, Motivasi Karir dan Persyaratan Akuntan Publik Terhadap Minat Mahasiswa Akuntansi Menjadi Akuntan Publik - faujiah dwi astuti; Andri Waskita Aji (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2021)
The purpose of this study was to examine the effect of economic motivation, career motivation, and requirements of public accountants on the interest of accounting students to become public accountants. The data used in this study are primary data from the results of distributing questionnaires in the form of google form. The population of this study were students of class 2017-2018 Accounting Study Program, Faculty of Economics, Sarjanawiyata Tamansiswa University, Yogyakarta. The data used in this study were 88 respondents. The sampling technique used the snowball sampling technique. This study uses data analysis techniques using multiple linear regression techniques. The results of this study indicate that economic motivation has no effect on the interest of accounting students to become public accountants, while career motivation and requirements for public accountants have a positive effect on the interest of accounting students to become public accountants.